Peningkatan Kebugaran Jasmani Dan Aktivitas Fisik Murid Melalui Permainan Tradisional Bentengan Dalam Pembelajaran Pjok: Penelitian Tindakan Kelas - Shohibul Ulum; Seida Kurnianto; Sita Dwi Nurmaharani; Sofia Isna Rahmadhani; Wahyu Luhur Pamujo; Wikan Tejo Purwito; Endang Mastuti Rahayu; Farid Ma'ruf (Performa, 2026)
This study aims to improve pupils’ physical fitness and physical activity through the incorporation of the traditional game of ‘bentengan’ into Physical Education, Sport and Health lessons. The method used in this study was Classroom Action Research, conducted in two cycles comprising planning, implementation, observation and evaluation. The subjects of this study were 36 pupils comprising 16 boys and 20 girls from Class VIII-D at State Junior High School 12, Surabaya. Data were obtained through physical fitness tests, knowledge assessments, behavioural observations, and pupil response questionnaires. The findings of this study indicate that there was an improvement in all elements of learning. The achievement rate in the cognitive aspect increased from 28% in the initial phase to 92% in Cycle II. In the psychomotor aspect, the achievement rate for the 30-metre run rose from 36% to 83%, for the shuttle run from 36% to 81%, and for the beep test from 50% to 92%. Affective observations showed that the majority of pupils were in the ‘good’ and ‘very good’ categories. Furthermore, pupils responded positively to lessons involving the traditional game of ‘bentengan’. In other words, the traditional game of ‘bentengan’ proved effective in improving pupils’ physical abilities and physical activity within the context of Physical Education lessons.